Further evidence for linkage of bipolar disorder to chromosomes 6 and 17 in a new independent pedigree series - Greenwood, Tiffany A (2012)
OBJECTIVES: We have previously reported the results of a linkage analysis of bipolar disorder in an initial set of 20 pedigrees ascertained through collaboration among three sites. We now report the results of our genomewide linkage analysis in an independent sample of 34 pedigrees segregating bipolar disorder. METHODS: Families were ascertained through a bipolar I or II disorder proband for the presence of bipolar I disorder, bipolar II disorder, or recurrent major depression in at least two other family members. A total of 440 markers at an average spacing of 8 cM were genotyped in 229 family members using fluorescent methods. RESULTS: Initial nonparametric analyses of chromosomes 6 and 17 provided evidence for a modest replication of linkage to these chromosomes previously reported in other studies. Additional analyses using multipoint parametric methods provided further evidence to support the 6q25 region with a heterogeneity LOD score of 3.28. Evidence from two-point parametric analyses also provides a modest replication of our previous findings of linkage to the 23 cM region of chromosome 22q13 in our original University of California, San Diego sample of 20 families and 57 families from the National Institute of Mental Health bipolar disorder sample. CONCLUSIONS: Our results suggest replication of some reported linkage peaks, such as 6q25 and 17p12; however, other peaks from our own previous study, such as 5p15, 13q32, and 22q13, were either not replicated or were only modestly replicated in these analyses.